STUDI KESESUAIAN LAHAN PESISIR UNTUK TAMBAK DI KECAMATAN NGOMBOL KABUPATEN PURWOREJO - Bambang Triyatmo (Universitas Gadjah Mada, 2001)
The objective of this study was to know the feasibility of the coastal area for shrimp and fish pond based on physical, chemical and biological parameters of soil and water as well as topographycal situation.The results of the study indicated that : .i). the coastal area in Ngombol district Purworejo regency was suitable for pond, .ii). the area have two kinds of land units, namely clay alluvial and sandy land units, iii). the former one was suitable for conventional pond constraction, fertile and acid soil, .iv). the latter was unsuitable for conventional pond constraction, unfertile and slightly-netral soil, .v). the water for shrimp and fish culture might be supplied from Cokroyasan and Lereng rivers (fresh-brackiswater), well (freshwater), and directy from intestidal zone for seawater.vi). in general, the water quality were suitable for shrimp and fish culture.This study suggested that in the clay alluvial soil, extensive and intensive ponds might be developed. However, intensive pond should be developed in the area with sandy soil.